MINIMALISASI SAMPAH PLASTIK DI KAMPUNG JAWA MELALUI GERAKAN “DIET SAMPAH PLASTIK” - Karina Karina; Taufiq Ihsan (BULETIN ILMIAH NAGARI MEMBANGUN, 2019)
Plastic has become a thing that we often encounter in everyday life. Various household appliances, cutlery, school equipment, and others still make plastic as the primary material. Plastic waste is the most challenging rubbish to be decomposed by soil naturally. Even in the span of years, the land will not succeed in breaking down plastic waste into organic compounds that can be reused by nature. Contrary to this, the consumption of plastic goods continues to increase every year, not least in the village of Kampung Jawa, Solok City. People who still choose to use plastic materials are the leading cause of the large amount of plastic waste produced by this village office. Through the Community Student Service Andalas University 2018, the "plastic waste diet" method has been carried out in the community. This movement aims to increase public awareness about the dangers of plastic waste to the environment and the importance of good habits to minimize plastic waste production. This method is socialized through counseling conducted to provide education to the community. The advice was chosen as an effective and efficient activity method to create good habits to minimize plastic waste. The counseling activities carried out successfully increased public awareness in reducing plastic waste. The community is interested in independently managing plastic waste produced in the surrounding environment, from collection to processing plastic waste into useful items. Community education and intelligence in managing plastic waste are very much needed; even minimizing plastic waste needs to be instilled early on to achieve a clean, healthy, and comfortable environment.